A comprehensive overview of clinical research on dexmedetomidine in the past 2 decades: A bibliometric analysis - Kong, Hao; Li, Mo; Deng, Chun-Mei; Wu, Yu-Jia; He, Shu-Ting; Mu, Dong-Liang (Frontiers in Pharmacology, 2023)
Dexmedetomidine is a potent, highly selective α-2 adrenoceptor agonist with sedative, analgesic, anxiolytic, and opioid-sparing properties. A large number of dexmedetomidine-related publications have sprung out in the last two decades. However, no bibliometric analysis for clinical research on dexmedetomidine has been published to analyze hot spots, trends, and frontiers in this field. The clinical articles and reviews related to dexmedetomidine, published from 2002 to 2021 in the Web of Science Core Collection, were retrieved on May 19, 2022, using relevant search terms. VOSviewer and CiteSpace were used to conduct this bibliometric study. The results showed that a total of 2299 publications were retrieved from 656 academic journals with 48549 co-cited references by 2335 institutions from 65 countries/regions. The United States had the most publications among all the countries (n = 870, 37.8%) and the Harvard University contributed the most among all institutions (n = 57, 2.48%). The most productive academic journal on dexmedetomidine was Pediatric Anesthesia and the first co-cited journal was Anesthesiology. Mika Scheinin is the most productive author and Pratik P Pandharipande is the most co-cited author. Co-cited reference analysis and keyword analysis illustrated hot spots in the dexmedetomidine field including pharmacokinetics and pharmacodynamics, ICU sedation and outcome, pain management and nerve block, and premedication and use in children. The effect of dexmedetomidine sedation on the outcomes of critically ill patients, the analgesic effect of dexmedetomidine, and its organ protective property are the frontiers in future research. This bibliometric analysis provided us with concise information about the development trend and provided an important reference for researchers to guide future research.